Heat-mass transfer properties with nonlinear stratification and zero mass flux in Maxwell nanofluid stagnation flow over a Riga surface - Khan, Abbas; Hashim; Farooq, Muhammad; Jamshed, Wasim; Mohamed Isa, Siti Suzilliana Putri; Hussain, Syed M. (Elsevier, 2025)
Researchers have been fascinated by non-Newtonian materials because of their exceptional qualities and extensive use in environmental, biomedical, and industrial activities. The Maxwell fluid model, renowned for being viscoelastic, provides essential insights into how non-Newtonian fluids behave under intricate flow conditions. Motivated by such potential uses, this work uses the two-dimensional Maxwell model with the nanofluid Buongiorno model to investigate the transport dynamics of nanoparticles, taking into account Brownian motion effects and thermophoresis. The study focuses on a variable-thickness Riga plate, which is commonly used in boundary layer control, microfluidics, and aviation. Furthermore, a fluid that is chemically reactive is examined across a stretching surface. Additionally, with applications in chemical reactors, energy systems, and medicines, this work investigates heat generation/absorption, nonlinear stratification, thermal radiation, and stagnation point flow. Reactive flow dynamics can be better understood through chemical reactions and zero mass flux circumstances. The fluid model incorporates the governing nonlinear equations for temperature, velocity, and concentration of nanoparticles. By using the boundary layer approximation, these equations undergo appropriate transformations to become nonlinear, dimensionless ordinary differential equations. For precise computation, the built-in ND Solve function is implemented to provide the solutions for the ODE system. An analysis and visual representation of the flow behavior, temperature, and concentration profiles are provided due to the related effective parameters. Moreover, surface drag force and the rate of heat and mass transfer at the surface are carefully investigated. According to the study's main findings, the Deborah and modified Hartmann parameters increase nanofluid velocity, while the wall thickness parameter falls. As thermophoresis and Brownian motion rise, fluid temperature increases; but, as thermal stratification rises, fluid temperature falls. Furthermore, the concentration profile is reduced with the enhancement of the Lewis and chemical reaction constraints. The excellent verification of the current numerical findings is proved by the consistency of the current values with previous literature in the same field.